Fiscal Policy, Public Expenditure Composition, and Growth : Theory and Empirics - Semmler, Willi; Greiner, Alfred; Diallo, Bobo; Rezai, Armon; Rajaram, Anand (World Bank, Washington, DC, 2012)
This paper responds to the development policy debate involving the World Bank and the IMF on the use of fiscal policy not only for economic stabilization but also to promote economic growth and increase per capita income. A key issue in this debate relates to the effect of the composition of public expenditure on economic growth. Policy makers and some researchers have argued that expenditure on growth-enhancing functions could enhance future revenue and justify the provision of "fiscal space" in the budget. But there are no simple ways to identify the growth-maximizing composition of public expenditure. The current paper lays out a research strategy to explore the effects of fiscal policy, including the composition of public expenditure, on economic growth, using a time series approach. Based on the modeling strategy of Greiner, Semmler and Gong (2005) we develop a general model that features a government that undertakes public expenditure on (a) education and health facilities which enhance human capital, (b) public infrastructure such as roads and bridges necessary for market activity, (c) public administration to support government functions, (d) transfers and public consumption facilities, and (e) debt service. The proposed model is numerically solved, calibrated and the impact of the composition of public expenditure on the long-run per capita income explored for low-, lower-middle- and upper-middle-income countries. Policy implications and practical policy rules are spelled out, the extension to an estimable model indicated, a debt sustainability test proposed, and the out-of-steady-state dynamics studied.